2013
DOI: 10.1161/hypertensionaha.113.01767
|View full text |Cite
|
Sign up to set email alerts
|

miR-30a Regulates Endothelial Tip Cell Formation and Arteriolar Branching

Abstract: Microvascular rarefaction increases vascular resistance and pressure in systemic arteries and is a hallmark of fixed essential hypertension. Preventing rarefaction by activation of angiogenic processes could lower blood pressure. Endothelial tip cells in angiogenic sprouts direct branching of microvascular networks; the process is regulated by microRNAs, particularly the miR-30 family. We investigated the contribution of miR-30 family members in arteriolar branching morphogenesis via delta-like 4 (Dll4)-Notch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 29 publications
0
51
1
Order By: Relevance
“…Together, these molecular and genetic studies have revealed that branching morphogenesis appears to be controlled by a conserved set of molecules, including fibroblast growth factors (FGFs), which signal through the mitogen-activated protein kinase (MAPK) cascade. Recent studies have also indicated a role for miRNAs in branching morphogenesis of the lung, kidney, salivary gland and vasculature (Biyashev et al, 2012;Chu et al, 2014;Hayashi et al, 2011;Jiang et al, 2013;Mujahid et al, 2013;Rebustini et al, 2012;Yu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these molecular and genetic studies have revealed that branching morphogenesis appears to be controlled by a conserved set of molecules, including fibroblast growth factors (FGFs), which signal through the mitogen-activated protein kinase (MAPK) cascade. Recent studies have also indicated a role for miRNAs in branching morphogenesis of the lung, kidney, salivary gland and vasculature (Biyashev et al, 2012;Chu et al, 2014;Hayashi et al, 2011;Jiang et al, 2013;Mujahid et al, 2013;Rebustini et al, 2012;Yu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…miR-484 suppresses the translation of the mitochondrial fission protein Fis1, and consequently inhibits Fis1-mediated fission and apoptosis in cardiomyocytes and adrenocortical cancer cells (Wang et al, 2012). miR-378 enhances cell survival and promotes angiogenesis by targeting Sufu and Fus1 expression (Lee et al, 2007), and miR-30 inhibits mitochondrial fission and the consequent apoptosis by suppressing p53 expression (Li et al, 2010), and stimulates arteriolar branching by directly targeting the Notch ligand Delta-like 4 (Dll4) (Jiang et al, 2013). All of these miRNAs were downregulated in the cutaneous wounds of STZ-induced diabetic rats in our study, suggesting that alterations may contribute to impaired wound healing by increasing cell apoptosis and inhibiting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the over expression of miR-30a promoted chondrogenic differentiation via down-regulating the expression of Delta-like 4 (DLL4, a ligand of the Notch signaling family) [27]. In addition, miR-30a stimulates arteriolar branching by abrogating endothelial DLL4, consequently controlling endothelial tip cell behavior [28]. As demonstrated, glioma cell invasion could be boosted by miR-30a through repressing neural cell adhesion molecule (NCAM) [29].…”
Section: Biological Function Of Mir-30a Genementioning
confidence: 99%